2008
DOI: 10.1590/s0103-50532008000500027
|View full text |Cite
|
Sign up to set email alerts
|

Copper adsorption as a function of solution parameters of variable charge soils

Abstract: Os efeitos do pH e da força iônica (I) sobre a adsorção de cobre (Cu) e a força direcional da reação em solos com cargas variáveis foram avaliados a partir de experimentos tipo "batch". Os resultados foram ajustados pelo modelo de Langmuir e, de acordo com as isotermas de adsorção, a afinidade de Cu (K L ) foi maior nas amostras do subsolo (0,061-0,468 L kg -1 ) do que na camada superficial (0,169-0,359 L kg -1 ). A adsorção máxima variou de 1114-2422 mg kg -1 (superfície) a 1002-1334 mg kg -1 (subsolo). Foi o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 55 publications
(115 reference statements)
1
22
0
4
Order By: Relevance
“…Soil pH decreases at increased metal concentrations during single-and multi-element sorption can be attributed to the hydrolysis effect and release of H + from soil sorption sites (Ponizovsky et al 2007, Mouta et al 2008. As adverted in Figure 4, pH decrease during single-element sorption at equilibrium was the most pronounced for Cu and followed the order Pb > Zn > Cd.…”
Section: Resultsmentioning
confidence: 88%
“…Soil pH decreases at increased metal concentrations during single-and multi-element sorption can be attributed to the hydrolysis effect and release of H + from soil sorption sites (Ponizovsky et al 2007, Mouta et al 2008. As adverted in Figure 4, pH decrease during single-element sorption at equilibrium was the most pronounced for Cu and followed the order Pb > Zn > Cd.…”
Section: Resultsmentioning
confidence: 88%
“…In both cases, adsorption reactions can be described mathematically by determining the Gibbs free energy (Silveira et al, 1999;Dias et al, 2003;Soares et al, 2005;Casagrande et al, 2008;Mouta et al, 2008;:…”
Section: Thermodynamic Parameters Of Adsorption Reactionmentioning
confidence: 99%
“…The Langmuir isotherm, fitted by nonlinear models, was successfully applied in the study of metals in Oxisols, including Ni (Camargo et al, 1989;Pombo et al, 1989). However, metal adsorption modeling in tropical soils is rarely accompanied by a more detailed description, based on thermodynamics concepts (Silveira et al, 1999;Dias et al, 2003;Soares et al, 2005;Iglesias et al, 2007;Casagrande et al, 2008;Mouta et al, 2008;. Some information has been obtained on thermodynamic modeling for the adsorption reaction of some metallic ions by homogeneous surfaces, such as kaolinite and oxidic interfaces (James and Healy, 1972;Angove et al, 1999;Trivedi and Axe, 2000), but there are few data on the thermodynamics of the Ni adsorption reaction in the soils (Sen Gupta and Bhattacharyya, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the difference between the PZSE values of the soil samples studied by Moreira et al (2008) was similar to that observed in this study, supporting the above hypothesis. According to the results of Silveira and Alleoni (2003), Casagrande, Soares and Mouta (2008), Mouta, Soares and Casagrande (2008), and Soares, Casagrande and Mouta (2009), the higher amounts of metals adsorbed in topsoil horizons are correlated to the organic matter content. Soil organic matter may be responsible for 50 to 95% of the cation exchange capacity (CEC) in Brazilian Oxisols, whose inorganic fraction is predominantly composed by low reactive minerals Alleoni, 2008).…”
Section: Resultsmentioning
confidence: 98%